An analysis of neurovascular disease markers in the hippocampus of Tupaia chinensis at different growth stages - Ouyang, Yiqiang; Zhang, Ying; Guo, Xiaoping; Li, Jiafu; Ao, Qingqing; Guo, Songchao; Zhang, Mingyuan; Sun, Junming (Frontiers in Neurology, 2023)
It is considered that Tupaia chinensis can replace laboratory primates in the study of nervous system diseases. To date, however, protein expression in the brain of Tupaia chinensis has not been fully understood. Tupaia chinensis of three age groups –15 days, 3 months and 1.5 years – were selected for studying protein expression profiles in their hippocampus. Observation showed a significant difference between the 15-day group and the other two groups, while the difference between the 3-month group and the 1.5-year group was not significant. This indicates that the protein expression of hippocampus of Tupaia chinensis begins to stabilize at the age of three months. KEGG analysis found that differential proteins can be enriched in several pathways related to neurovascular diseases, such as metabolic pathway, Alzheimer's disease, Huntington's disease, Parkinson's disease, etc. KEGG enrichment analysis also showed that relevant proteins involved in oxidative phosphorylation in the hippocampus of Tupaia chinensis on 15-day were generally down-regulated, and the ribosomal proteins were up-regulated, comparing to those in the hippocampi of the other two groups. This suggested that when the Tupaia chinensis hippocampus was developing during the period from the 15th day to 3 months, the expression of oxidative phosphorylated proteins and ribosomal proteins would vary over time, while the protein expression profile in the hippocampus of Tupaia chinensis after 3 months had become stable. Moreover, the study underlines that during the early development of the hippocampus of Tupaia chinensis, the energy demand is increasing while the protein synthesis is decreasing. The mitochondria of Tupaia chinensis changes with age, and the oxidative phosphorylation metabolic pathway of mitochondria is closely related to neurovascular diseases, such as stroke and cerebral ischemia.